Neisseria meningitidis has acquired sequences within the capsule locus by horizontal genetic transfer - Clemence, MEA; Harrison, OB; Maiden, MCJ (F1000Research, 2019)
Background: Expression of a capsule from one of serogroups A, B, C, W, X or Y is usually required for Neisseria meningitidis (Nme) to cause invasive meningococcal disease. The capsule is encoded by the capsule locus, cps, which is proposed to have been acquired by a formerly capsule null organism by horizontal genetic transfer (HGT) from another species. Following identification of putative capsule genes in non-pathogenic Neisseria species, this hypothesis is re-examined.